The effect of the 135.6 nm emission originated from the ionosphere on the TIMED/GUVI O/N2 ratio. Issue 2 (15th February 2013) - Kil, H.; Lee, W. K.; Shim, J.; Paxton, L. J.; Zhang, Y.
Abstract : [1] The column number density ratio of atomic oxygen to molecular nitrogen (O/N2 ratio) provided by the Global Ultraviolet Imager (GUVI) onboard the Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics (TIMED) satellite has been used as a diagnostic of the thermospheric neutral composition. However, a recent study claimed that the GUVI O/N2 ratio is not a pure thermospheric parameter in low latitudes during periods of low geomagnetic activity. This study quantifies the O/N2 ratio contamination by the ionosphere using the GUVI observations and model ionosphere acquired from 31 August to 2 September 2002. During this period, the local time of the GUVI observation was near 1500 and the average Kp index was 2°. The 135.6 nm emission originated from the ionosphere is estimated using the electron density profiles provided by the Utah State University‐Global Assimilation of Ionospheric Measurements model. Our results show that the 135.6 nm emission originated from the equatorial ionization anomaly (EIA) contributes 5 ~ 10% to the total 135.6 nm intensity and O/N2 ratio. The EIA feature and longitudinal wave patterns in the GUVI 135.6 nm intensity maps are identified above an altitude of 300 km and show a good agreement with those in the F region plasma density. However, the EIA feature and longitudinal wave patterns do not appear in the GUVI 135.6 nm intensity maps below an altitude of 300 km and in the GUVI N2 Lyman‐Birge‐Hopfield band intensity maps in any altitude. These observations indicate that the longitudinal wave patterns in the GUVI O/N2 ratio represent the ionospheric phenomenon. Key Points: Ionospheric signatures exist in the GUVI O/N2 ratio Equatorial ionization anomaly contributes 5–10% to the O/N2 ratio Wave patterns in the GUVI O/N2 ratio represent ionospheric phenomenon